Evaluation of midazolam as intravenous induction agent for anaesthesia in dogs - RAFEE, MALIK ABU; KINJAVDEKAR, PRAKASH; AMARPAL; AITHAL, H P (The Indian Journal of Animal Sciences, 2017)
A randomized, blinded, clinical study was conducted on 24 healthy mixed breed female dogs to evaluate midazolam as an induction agent for anaesthesia and its effect on vital parameters during elective ovariohysterectomy. Animals were administered atropine and divided randomly into groups D, DB and DP and premedicated with dexmedetomidine, dexmedetomidine and butorphanol, and dexmedetomidine and pentazocine, respectively. After 10 min of premedication, anaesthesia was induced with midazolam (0.8 mg/kg IV), in all the groups and maintained with 1% ketamine as and when needed. Time loss of pedal reflex was considered as the time of induction and it was recorded as 5.00±3.12, 4.75±2.92 and 4.75A±2.66 min in groups D, DB and DP, respectively. Laryngeal reflex was abolished completely, permitting intubation in all the groups. Recovery was smooth and uneventful and recovery time and duration of anaesthesia were comparable in all the groups. Heart rate showed an initial increase followed by a decrease, while respiratory rate decreased below the baseline in all the groups. SBP, DBP and MAP increased initially in all the groups and then decreased until 120 min interval. However, mean arterial pressure remained above the baseline throughout the observation period in all the groups. SpO2 decreased gradually from the baseline throughout the observation period. The results showed that midazolam at the rate of 0.8 mg/kg IV can be used safely as an induction agent in dogs premedicated with dexmedetomidine alone or with butorphanol or pentazocine while preserving the vital parameters.